2020
DOI: 10.3390/children7120267
|View full text |Cite
|
Sign up to set email alerts
|

Contextual Complexities in Implementing a Family-Based Childhood Obesity Intervention: The Perspectives of Enrolled Children and Their Parents

Abstract: Family interventions to treat childhood obesity are widely used, but knowledge about how family dynamics are affected by these interventions is lacking. The present study aims to understand how a family intervention impacts the context of family dynamics, and how different contexts affect the families’ implementation of the intervention. Based on qualitative interviews, we studied families with a child between 9–12 years enrolled in a family intervention to treat childhood obesity at a pediatric outpatient cli… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
12
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 35 publications
1
12
0
Order By: Relevance
“…Several studies also revealed that the role of tradition and parental perception have a significant impact on the health status of children. Most mothers in middle-income countries perceived that other family members would be concerned and criticized if their child was slim [67,68]. A thin child was more likely to be perceived as coming from a poor family by others in Bangladesh [68].…”
Section: Discussionmentioning
confidence: 99%
“…Several studies also revealed that the role of tradition and parental perception have a significant impact on the health status of children. Most mothers in middle-income countries perceived that other family members would be concerned and criticized if their child was slim [67,68]. A thin child was more likely to be perceived as coming from a poor family by others in Bangladesh [68].…”
Section: Discussionmentioning
confidence: 99%
“…Childhood obesity is associated with an increased risk of chronic diseases, such as cardiovascular disease and diabetes mellitus and also has a profoundly negative effect on children's psychological health 3,18,20,26 . Several sociodemographic and family environment characteristics, such as prenatal practice, socioeconomic status, and parental behavior, were found to be associated with the risk of obesity/overweight among children 3,19,21,24,27 . According to Nielsen et al carried out in Denmark, families with ethnic minority status are more likely to have the child's grandparents as a source of knowledge regarding food 28 .…”
Section: Nutritional Influencementioning
confidence: 99%
“…The eating habits of children up to 12 years of age are significantly influenced by the family 26 . The family's eating environment includes the children's actual feeding practices, their eating habits, as well as the beliefs and attitudes they verbally convey about healthy nutrition and promoted eating behavior 3,27,30,31 . Including, food preparation by grandparents is observed by the grandchildren and 30 , as a consequence, in adulthood, grandchildren run on similarly 30,32 .…”
Section: Nutritional Influencementioning
confidence: 99%
“…Therefore, comprehensive assessment of health and psychosocial stress and uptake through early prevention programs is viewed as critical to improving children's health ( 11 , 12 ). Research has found that despite the availability of preventive programs aimed at improving dietary intake, physical activity, and psychosocial well-being, attendance and adherence to these programs are low ( 1 , 13 ).…”
Section: Introductionmentioning
confidence: 99%